Purification of a cortical complex containing two unconventional actins from Acanthamoeba by affinity chromatography on profilin-agarose (The Rockefeller University Press, 1994)
We identified four polypeptides of 47, 44, 40, and 35 kD that bind to profilin-Sepharose and elute with high salt. When purified by conventional chromatography using an antibody to the 47-kD polypeptide, these four polypeptides copurified as a stoichiometric complex together with three additional polypeptides of 19, 18, and 13 kD that varied in their proportions to the other polypeptides. Partial protein sequences showed that the 47-kD polypeptide is a homologue of S. pombe act2 and the 44-kD polypeptide is a homologue of S. cerevisiae ACT2, both unconventional actins. The 40-kD polypeptide contains a sequence similar to the WD40 motif of the G beta subunit of a trimeric G-protein from Dictyostelium discoideum. From partial sequences, the 35-, 19-, and 18-kD polypeptides appear to be novel proteins. On gel filtration the complex of purified polypeptides cochromatograph with a Stokes' radius of 4.8 nm, a value consistent with a globular particle of 220 kD containing one copy of each polypeptide. Cell extracts also contain components of the complex that do not bind the profilin column. Affinity purified antibodies localize 47- and 18/19-kD polypeptides in the cortex and filopodia of Acanthamoeba. Antibodies to the 47-kD unconventional actin cross-react on immunoblots with polypeptides of similar size in Dictyostelium, rabbit muscle, and conventional preparations of rabbit muscle actin but do not react with actin.